Efficacy and safety of the early implementation of a multimodal rehabilitation program in mechanically ventilated patients: A randomized clinical trial protocol. - Jorge Iván Alvarado Sánchez; Laura Maria Castillo Morales; Yenny Rocio Cardenas Bolivar; Valentina Montañez Nariño; Maria Valentina Stozitzky Ríos; Catherine Lissell Arévalo Guerrero; Miguel Leonardo Pulido Bobadilla; Diana Marcela Melo Rojas; Ana Gabriela López Rubio; Diana Carolina Ortíz Moreno; Paula Andrea Barreto Garzón; Marisol Murillo; et al. (PLoS ONE)
Background Intensive care unit-acquired weakness (ICUAW) and post-intensive care syndrome (PICS) are significant complications among critically ill patients, leading to prolonged hospital stays, increased healthcare costs, and reduced quality of life. Early physical therapy in the ICU has shown promise in mitigating these adverse outcomes, yet randomized controlled trials (RCTs) evaluating the combined effects of physical, respiratory, occupational, and speech therapy initiated within the first 24-72 hours are lacking. Methods This single center, controlled clinical trial aims to establish the efficacy and safety of an early multimodal rehabilitation program (MRP) compared with a late MRP in mechanically ventilated patients admitted to the ICU. Adult patients (≥18 years) with a Barthel score ≥70 and requiring invasive mechanical ventilation for more than 24 hours will be included. Participants will be randomly assigned to early MRP, initiated within 24 hours post-intubation, or late MRP, starting 72 hours post-intubation. The primary outcome is the duration of mechanical ventilation. Safety will be assessed by comparing the number of adverse events between groups. The MRP includes passive and active interventions from physical, speech, respiratory, and occupational therapy teams. Therapy intensity and type are adjusted according to the patient's Richmond Agitation-Sedation Scale (RASS) score. Patients with lower RASS scores (indicating deeper sedation) will receive primarily passive interventions (e.g., passive range-of-motion exercises), while those with higher RASS scores (indicating lighter sedation or alertness) will engage in more active therapies (e.g., active-assisted exercises and functional mobility activities). For patients with RASS ≥2, occupational therapy will focus on behavioral and environmental modulation, employing calming techniques, sensory stimuli, and cognitive tasks, with family education to support spatiotemporal orientation. This adaptive approach ensures patient safety and optimizes therapy based on the patient's current sedation level and clinical condition. Dissemination The results will be published in peer-reviewed journals and presented at conferences. Trial registration ClinicalTrials.gov NCT06133504. Registered on November 11, 2023.